Characteristics and outcomes of fall-related open-globe injuries in pseudophakic patients - Kavoussi, Shaheen C (Clin Ophthalmol, 2015)
AIM: We aimed to identify the characteristics and prognostic indicators of poor visual and anatomic outcome in pseudophakic patients with fall-related open-globe (OG) injuries. We used a case series design, for a total of 26 patients. METHODS: Charts of consecutive pseudophakic patients with fall-related OG injury at a single institution were reviewed. Demographics, ophthalmic history, circumstances of injury, initial best-corrected visual acuity (BCVA), examination findings, surgical interventions, and follow-up BCVA were tabulated for statistical analysis with unpaired t-tests and Fisher’s exact tests. RESULTS: Nineteen patients (73%) were women. Mean (± standard deviation) age was 80.6±4.6 years (range: 61–97 years). Initial BCVA was <20/400 in 24 of 25 patients (96%). Mean ocular trauma score (OTS) was 38.54±10.95. OTS was lower (P=0.0017, P<0.0001, and P=0.0240) and wound size was larger (P=0.0440, 0.0145, and 0.0026) in patients with final BCVA <20/40, <20/400, and phthisis at final follow-up, respectively; compared to patients with BCVA ≥20/40, 20/400, and no phthisis at final follow-up, respectively. Final BCVA <20/400 was associated with 360° subconjunctival hemorrhage (SCH), retinal detachment, and proliferative vitreoretinopathy (P=0.0498, 0.0181, and 0.0310, respectively). Total hyphema, intraocular lens (IOL) damage, and IOL expulsion were associated with needing multiple surgical interventions (P=0.0345, P<0.0001, and P=0.0023, respectively). CONCLUSION: Large wound size, low OTS, 360° SCH, total hyphema, posterior injury, and IOL damage are common findings that are also prognostic of poor visual and anatomic outcome in pseudophakic patients with fall-related OG injuries. Ophthalmologists dealing primarily with geriatric populations should contribute to the discussion of fall risk.